2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319687
|View full text |Cite
|
Sign up to set email alerts
|

Cuffless blood pressure estimation from the carotid pulse arrival time using continuous wave radar

Abstract: Ambulatory blood pressure monitors based on pulse transit time are limited by the challenge of changing vascular tone. This study focuses on the use of the carotid artery as an alternative location for arterial pulse acquisition. We use continuous wave radio frequency (RF) radar coupled directly to the body to detect the pulse wave signal. We have shown that the blood pressure-pulse transit time calibration using the carotid pulse is as accurate as that of the radial arterial pulse. The results of this investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Most importantly, this study further analysed the estimation accuracy of the three machine learning algorithms under different BP categories (normotensive, hypertensive, and hypotensive) and found that most of the algorithms exhibited better accuracy in the normotensive category. Previous research only presented overall BP accuracies (overall mean of difference ± SD of difference) rather than individual categorical BP accuracies [ 3 , 9 , 36 ]. Some studies only included normotensive subjects [ 10 , 17 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most importantly, this study further analysed the estimation accuracy of the three machine learning algorithms under different BP categories (normotensive, hypertensive, and hypotensive) and found that most of the algorithms exhibited better accuracy in the normotensive category. Previous research only presented overall BP accuracies (overall mean of difference ± SD of difference) rather than individual categorical BP accuracies [ 3 , 9 , 36 ]. Some studies only included normotensive subjects [ 10 , 17 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…MLR is a type of the machine learning algorithm that has been widely used by previous researchers to estimate cuffless BP [ 3 , 7 , 26 ]. The algorithm started with the random selection of coefficients of the linear algorithm ( θ 0 , θ 1 , θ 2 , and θ 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of human breathing can range anywhere from 0.1 to 0.5 Hz [9]. Data in the receiver will be a phase-shifted signal, which will include respiration information [10]. A field-programmable gate array (FPGA)-based system was designed and implemented to detect human heartbeat and respiration using Doppler processing.…”
Section: Introductionmentioning
confidence: 99%
“…The systems developed by [2,10,11,15,16,17] were used to measure vital signs, but only in lying or seated positions. The experiments in [4,19,20,21] were done in standing and walking positions; however, only one subject took part in each test.…”
Section: Introductionmentioning
confidence: 99%